Handleiding voor de determinatie van harde dierlijke materialen Bot, gewei, ivoor, hoorn, schildpad, balein en hoef - Rijkelijkhuizen, Marloes (Amsterdam University Press, 2008)
Is an object made from bone or ivory? Was an elephant, walrus or hippo's tusk used to in the production? In this book the author illustrates how the various materials of animal origin can be recognized. All hard animal material, bones, antlers, ivory, horns, tortoise shells, whalebones and hoofs are examined. This book details the building blocks and structure; it's distinctive features and a brief history of the use of these materials from the late prehistory to the 18th century Netherlands. This resourceful book is not only useful for archaeologists and museum conservators but also for the general public with a curious mind.